2001
DOI: 10.1037/0022-006x.69.4.699
|View full text |Cite
|
Sign up to set email alerts
|

Advances in empirically based assessment: Revised cross-informant syndromes and new DSM-oriented scales for the CBCL, YSR, and TRF: Comment on Lengua, Sadowski, Friedrich, and Fisher (2001).

Abstract: L. Lengua et al. (2001) proposed scoring the Child Behavior Checklist (CBCL; T. Achenbach, 1991b) on dimensions that "correspond to current conceptualizations of child symptomatology," (p. 695) embodied in the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV; 4th ed., American Psychiatric Association, 1994). They concluded that their "results support the use of the new dimensions." Yet, their regressions and diagnostic efficiency statistics showed that DSM diagnoses were predicted less well by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
332
0
18

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(358 citation statements)
references
References 4 publications
8
332
0
18
Order By: Relevance
“…The original empirical syndrome scales for the CBCL that were used in our previous study, were based on multivariate statistical analysis on data from large samples. To fit more closely with the clinical-diagnostic approach represented by the DSM (APA, 2006), six new DSM-IV scales were recently constructed: Affective Problems, Anxiety Problems, Somatic Problems, Attention Deficit/Hyperactivity Problems (ADH), Oppositional Defiant Problems (OD), and Conduct Problems (CD) (Achenbach and Dumenci, 2001;Achenbach et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The original empirical syndrome scales for the CBCL that were used in our previous study, were based on multivariate statistical analysis on data from large samples. To fit more closely with the clinical-diagnostic approach represented by the DSM (APA, 2006), six new DSM-IV scales were recently constructed: Affective Problems, Anxiety Problems, Somatic Problems, Attention Deficit/Hyperactivity Problems (ADH), Oppositional Defiant Problems (OD), and Conduct Problems (CD) (Achenbach and Dumenci, 2001;Achenbach et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…To fit more closely to the clinical diagnostic approach, represented by the DSM [7], the following DSM-IV scales were recently constructed for the CBCL and its derivatives [4,5]: Affective Problems, Anxiety Problems, Somatic Problems, Attention Deficit/Hyperactivity Problems, Oppositional Defiant Problems, and Conduct Problems. These CBCL/YSR DSM-IV scales are constructed based on the opinion of experts from 11 different countries from all over the world.…”
Section: Methodsmentioning
confidence: 99%
“…Research has suggested that maladaptive functioning in childhood and adolescence falls into two categories of disorders: internalizing and externalizing (Achenbach, 1991;Achenbach & Dumenci, 2001). The current study focused only on adolescents' perceptions of their internalizing behavior problems like depression, anxiety, and social withdrawal, which were shown to increase in prevalence during adolescence and continue to increase into adulthood (Lee & Hankin, 2009;Steinberg & Morris, 2001).…”
Section: Adolescents' Socioemotional Adjustmentmentioning
confidence: 99%